The chemical evolution of brine and Mg-K-salts along the course of extreme evaporation of seawater – An experimental study. (15th November 2018) - Shalev, Netta; Lazar, Boaz; Köbberich, Michael; Halicz, Ludwik; Gavrieli, Ittai
Abstract: Extreme evaporation experiments of modern seawater, up to a degree of evaporation (DE) of 870 on Li scale and brine density of 1.40 g·ml −1 were conducted under controlled semi-natural conditions. This DE is well within the bischofite facies and, to the best of our knowledge, is the highest experimental DE ever reported. During the experiments, brine temperature varied between ∼20 °C and ∼40 °C with few excursions to higher temperatures, thereby demonstrating the effect of temperature on the precipitating mineral assemblages. Results were compared to a thermodynamic simulation of the evaporation experiment at 25 °C, based on the Harvie-Møller-Weare activity coefficients correction. The relative amounts of the precipitated minerals were evaluated from the bulk chemical composition of the collected precipitates, applying a Li-based methodology for subtracting the contribution of the brine adsorbed on the precipitated salts. The following minerals were identified during the evaporation experiments: halite (NaCl), epsomite (MgSO4 ∙7H2 O), kainite (KMgClSO4 ∙3H2 O), carnallite (MgKCl3 ∙6H2 O), kieserite (MgSO4 ∙H2 O) and bischofite (MgCl2 ∙6H2 O). The precipitation of the Mg-salts was accompanied by continuous halite precipitation up to DE of ∼170. The experimental results are in good agreement with literature experimental data, available up to DE = 98, and generally follow the thermodynamic calculations, thereby supporting both the established methodology of the experiments and the simulation parameters and assumptions. Minor differences between the experiments and the thermodynamic calculation are mainly due to temperature variations. The experiments suggest that, at warmer temperatures (∼50 °C), kainite and bischofite precipitate instead of kieserite, which precipitates to a greater extent at lower temperatures (25–30 °C). The presence of organic matter (OM) in the brine was found to reduce the evaporation rate and the final DE at which evaporation ceased, but not to significantly affect the chemical evolution of the brine. The detailed systematic data-set presented here is useful for both geochemical and applied purposes. For example, it can be used as a reference for reconstructing the evolution of ancient marine-derived brines, using evaporitic sequences far beyond the halite facies. Hence, this study provides new insights on the formation of such evaporitic minerals and opens the way for further studies on these highly soluble evaporitic sequences as clues to the chemical composition of the ancient oceans.